The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1002/ange.202205784
|View full text |Cite
|
Sign up to set email alerts
|

A Real‐Time In Situ Demonstration of Direct and Indirect Transformation Pathways in CdTe Magic‐Size Clusters at Room Temperature

Abstract: The transformations of colloidal semiconductor magic‐size clusters (MSCs) are expected to occur with only discrete, step‐wise redshifts in optical absorption. Here, we challenge this assumption presenting a novel, conceptually different transformation, for which the redshift is continuous. In the room‐temperature transformation from CdTe MSC‐448 to MSC‐488 (designated by the peak wavelengths in nanometer), the redshift of absorption monitored in situ displays distinctly continuous and/or step‐wise behavior. Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…The uninterrupted pattern is similar to that reported for the intracluster isomerization from CdTe MSC-448 to MSC-488. 36,37 After the addition of Cd(OA) 2 to a dispersion containing ZnSe MSC-299 at RT, the CE reaction (Step 2) that transfers the ZnSe PC to the CdSe PC takes place immediately. Step 2 facilitates Step 1 via which ZnSe MSC-299 transforms to its counterpart ZnSe PC-299.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The uninterrupted pattern is similar to that reported for the intracluster isomerization from CdTe MSC-448 to MSC-488. 36,37 After the addition of Cd(OA) 2 to a dispersion containing ZnSe MSC-299 at RT, the CE reaction (Step 2) that transfers the ZnSe PC to the CdSe PC takes place immediately. Step 2 facilitates Step 1 via which ZnSe MSC-299 transforms to its counterpart ZnSe PC-299.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In addition to the present CE reaction, we have demonstrated that the binary ME PC can experience another four chemical reactions. They are isomerization to binary ME MSCs, [2][3][4][5][14][15][16]18,34,35 substitution reactions followed by isomerization to binary or ternary MSCs (Figure S1B), 17,[34][35][36][37]53,54 addition reactions followed by isomerization to photoluminescent MSCs (Figure S1B), 55 and fragmentation to QDs. 2,56 For the reaction of M and E precursors to ME QDs, the E precursor dominates the selfassembly of the M and E precursors that results in the formation of the ME PC with similar stoichiometry.…”
Section: ■ Conclusionmentioning
confidence: 99%